Pengembangan video pembelajaran berbasis eksperimen untuk mengatasi loss-learning dalam pembelajaran IPA siswa sekolah dasar - Farida Nur Kumala; Arnelia Dwi Yasa; Adam Bin Haji Jait; Ira Wulandari (Jurnal Inspirasi Pendidikan, 2023)
This study aims to develop Experiment-Based Learning Videos to develop meaningful learning so as to increase students' understanding and activeness in learning science in grade V Elementary School. The research conducted was ADDIE development research, with research subjects being students of SDN Pulungdowo 2, a total of 50 students. The instruments used in this study were questionnaires, observation sheets and tests. Data analysis used quantitative descriptive and inferential, also qualitative descriptive. The results showed that Experiment-Based Learning Video Media which has been developed adequate with the feasibility, practicality and the effectivity. So, it can improve student activity and learning outcomes of students (Feasibility= 91%; Practicality= 89%; tactivity (47) = -16,32; tlearning outcome (47) = -12,34, p < 0,05, respectively). It can be concluded that learning video media experimental-based able to overcome loss-learning in students.